2020
DOI: 10.3390/foods9101419
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Aroma of Treixadura Wines during Bottle Aging

Abstract: Aroma is a crucial attribute for wine quality, particularly in white wines. Traditionally, the consumption of young white wines is recommended over the year following grape harvest due to potential aroma losses that would worsen wine quality. This study aimed to investigate the evolution of volatile compounds, odor activity value-based aroma notes, and sensory perception in Treixadura (Vitis vinifera L.) dry white wines during a 24-month bottle-aging period. Volatile composition was determined by gas chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The main terpenols in wine are geraniol, linalool, and α-terpineol [ 128 ] Albeit most aromatic terpenols originate from terpenoids in the grape skin, they can be newly formed during aging in bottle by acid-catalyzed hydrolysys from geraniol to linalool and/or α-terpenol through carbocation intermediates [ 102 ]. In the same way, it has been found that linalool may give place to geraniol by reduction with an hydroxyl anion [ 101 ] Linalool and α-terpineol have been reported to steadily increase at 18 months of storage but then show significant degradation after 24 months in Treixadura wines [ 129 ]. This kinetic behavior of terpenols has been also reported in many types of wines [ 130 ].…”
Section: Desired Chemical Changesmentioning
confidence: 98%
“…The main terpenols in wine are geraniol, linalool, and α-terpineol [ 128 ] Albeit most aromatic terpenols originate from terpenoids in the grape skin, they can be newly formed during aging in bottle by acid-catalyzed hydrolysys from geraniol to linalool and/or α-terpenol through carbocation intermediates [ 102 ]. In the same way, it has been found that linalool may give place to geraniol by reduction with an hydroxyl anion [ 101 ] Linalool and α-terpineol have been reported to steadily increase at 18 months of storage but then show significant degradation after 24 months in Treixadura wines [ 129 ]. This kinetic behavior of terpenols has been also reported in many types of wines [ 130 ].…”
Section: Desired Chemical Changesmentioning
confidence: 98%
“…On the other hand, bottle aging not only evolves a more fruity aroma and softer mouth-feel than oak barrel aging [ 9 ], but also leads to increased phenolic content compared to aging in steel tanks [ 10 ]. This remains a hot topic in the wine-making industry [ 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…e flavour profile of alcoholic wines has been found to contain higher alcohols and secondary metabolites like terpenes, monoterpenes, C-3 norisoprenoids, C-6 alcohols, among many others [79,80]. Studies have shown that these compounds are produced during the complete fermentation process and undergo biochemical interactions to produce a more pleasant flavour [38,46].…”
Section: Flavour Compounds Profile Of Nonalcoholic Versus Alcoholic Winesmentioning
confidence: 99%